Physicochemical and Biopharmaceutical Characterization of N-Iodomethyl-N,N-Dimethyl-N-(6,6-1 Diphenylhex-5-En-1-Yl) Ammonium Iodide and A Promising Antileishmania Delivery System (2018)
ABSTRACT: Cutaneous leishmaniasis (CL) is an infectious disease endemic in tropical and subtropical countries. The current drugs have severe drawbacks that restrict their use and enhance the need for better drugs. Recently, the N-iodomethyl-N,N-dimethyl-N-(6,6-diphenylhex-5-en-1-yl) ammonium iodide (C6I) was identified as a promising compound for the topical treatment of CL. The need for oral drugs with potential use to treat cutaneous, mucosal and visceral leishmaniasis, in the present work were determined the pharmaceutical and some biopharmaceutical properties of C6I as possible oral treatment and based on this results a nanoformulation was elaborated, characterized and tested in in vitro and in vivo model of the antileishmanial activity and toxicological assays. The C6I showed crystalline form and good intestinal permeability, its dissolution profile did not change with pH changes. The C6I was not mutagenic and genotoxic in vitro, it presented some minors acute toxicological effects. The solid lipid nanoparticles (SLN) used Precirol® as lipid, it had a size in the nano range scale with a low polydispersity index, and encapsulation efficiency > 60%. The nanoparticles of C6I (PC6I) increased the in vitro antileishmanial activity 40-fold than free C6I. In turn, the oral administration of C6I and PC6I (30 mg/kg/d, 28 days) produced complete cure in 42.9% and 71.4%, respectively, with no relapses and no toxicity. The effectiveness of meglumine antimoniate was 100% but the relapse rate was 28.6%. C6I and PC6I are safe compounds, as demonstrated in in vitro and in vivo assays for toxicological profile. In conclusion, a novel oral quaternary ammonium iodide salt-based formulation with antileishmanial properties was developed. The safety and effectiveness information of PC6I formulation showed here supports the further evaluation of efficacy and safety in patients to validate the use of PC6I as an alternative for the oral treatment of CL.